Preparation method of foamy copper-based composite material with photothermal effect
By loading nickel atoms on the surface of the foam copper matrix to modify the polydopamine/aniline composite organic matter and loading CeCo2Fe16O27 crystals, a foam copper-based composite material with excellent photothermal effect was prepared, which solved the problem of low efficiency of metronidazole sewage treatment in the prior art and achieved efficient metronidazole degradation.
Patent Information
- Application Number
- CN202411896863.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The prior art is difficult to efficiently treat metronidazole sewage, and the lack of materials that can effectively activate peracetic acid, resulting in low degradation efficiency of metronidazole.
By loading nickel atoms on the surface of the foamed copper matrix to modify the polydopamine/aniline composite organic matter and converting it into Ni(PDA)2(PANI)2 coordination polymer, and then loading CeCo2Fe16O27 crystals on its surface, a foamed copper-based composite material with excellent photothermal effect was prepared. This material can efficiently activate peracetic acid and promote the degradation of metronidazole.
The efficient degradation of metronidazole sewage is achieved, the peracetic acid activation efficiency is improved, and the oxidative degradation reaction rate of metronidazole is significantly improved.
Smart Images

Figure CN119708524A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metronidazole sewage treatment, in particular to a method for preparing a foam copper-based composite material with a photothermal effect for treating metronidazole sewage. Background Art
[0002] Metronidazole is a drug with a nitroimidazole ring structure. In the field of antiprotozoal drugs, it is widely used to treat balantidiasis, cutaneous leishmaniasis, dracunculiasis, etc. In the field of antibiotics, it is not only used to treat infections caused by anaerobic bacteria, including digestive system infections, respiratory system infections, bone tissue infections, reproductive system infections, etc., but also used to treat inflammations such as appendicitis, osteomyelitis, cholecystitis, liver abscesses, brain abscesses and empyema caused by anaerobic bacteria. With the development of the economy and the pharmaceutical industry, the demand for metronidazole and its production and use are increasing, and the production process of metronidazole will produce a large amount of metronidazole-containing wastewater. Metronidazole is soluble in water, difficult to biodegrade, and easy to migrate. Metronidazole can damage the function of human and animal nerve cells, interfere with the metabolic process of human and animal nerve cells, and has neurotoxicity; at the same time, metronidazole can irritate the gastrointestinal mucosa, damage the function of the digestive system, has digestive toxicity, and can affect erythrogenesis and metabolism, has blood toxicity, and can also cause allergic reactions in individuals, and has carcinogenicity. In short, metronidazole wastewater poses a great threat to the water environment and society.
[0003] The cleavage of the activated peracetic acid OO bond can produce peroxyacetyl radicals CH3C(O)OO·, acetoxy radicals CH3C(O)O· and ·OH radicals with strong oxidizing properties. These active radicals can degrade metronidazole-containing wastewater. In addition, the photothermal effect of the photothermal material can promote the cleavage of the peracetic acid OO bond, reduce the activation energy of peracetic acid, and then promote the generation of CH3C(O)OO·, CH3C(O)O· and ·OH radicals, thereby improving the degradation efficiency of metronidazole.
[0004] At present, in the field of metronidazole wastewater treatment, there is an urgent need to develop a treatment material for degrading metronidazole wastewater that has excellent photothermal effect and can efficiently activate peracetic acid. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a foam copper-based composite material with photothermal effect. The foam copper-based composite material prepared by the method has excellent photothermal effect and can efficiently activate peracetic acid to degrade metronidazole wastewater.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing a foam copper-based composite material with photothermal effect, comprising the following steps:
[0008] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter;
[0009] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer;
[0010] Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16 O 27 Crystal.
[0011] Preferably, the step [1] specifically includes the following operations:
[0012] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution; add azobisisoheptanenitrile to ethanol and mix to form an additive solution; mix the base solution and the additive solution in a certain proportion to form a reaction solution, immerse the foam copper sample in the reaction solution, heat to 110-130°C, react for 3-5 hours, take out the sample and wash it with deionized water to obtain a foam copper with a polydopamine / aniline composite organic compound loaded on the surface, recorded as intermediate A;
[0013] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution; immerse the intermediate A in the modification solution at room temperature for 4-6 hours, take out the sample and wash it with deionized water, and dry it at room temperature for 8-12 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0014] Preferably, in step a1, the amount of p-aminobenzoic acid added per liter of the base liquid is 20-50 g, the amount of m-phenylenediamine added is 70-110 g, the amount of dopamine hydrochloride added is 80-100 g, the amount of aminoacetic acid added is 10-25 g, and the amount of sodium hydroxide added is 15-30 g; the amount of azobisisoheptanenitrile added per liter of the additive liquid is 30-60 g; the volume ratio between the base liquid and the additive liquid in the reaction liquid is 9-11:2-3; the weight of the foamed copper immersed in each liter of the reaction liquid is 170-220 g.
[0015] Preferably, in step a2, the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 10-25 g; and the weight of the intermediate A immersed in each liter of the modification solution is 50-70 g.
[0016] Preferably, the step [2] specifically includes the following operations:
[0017] b1. Add nickel sulfate, N-methylaniline, sodium metabisulfite and dopamine hydrochloride to deionized water to form a coordination polymer construction solution;
[0018] b2. The intermediate B is immersed in the coordination polymer construction solution, heated to 50-90°C in a water bath, reacted for 10-14 hours, and dried at room temperature for 6-8 hours to obtain a foam copper with Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
[0019] Preferably, in step b1, the concentration of nickel sulfate in the polymer construction solution is 50-80 g / L, the concentration of sodium pyrosulfite is 20-30 g / L, and the concentration of dopamine hydrochloride is 40-70 g / L; and the amount of N-methylaniline added per liter of polymer construction solution is 10-50 ml.
[0020] Preferably, in step b2, the weight of the intermediate B immersed in each liter of the coordination polymer construction solution is 140-170 g.
[0021] Preferably, the step [3] specifically includes the following operations:
[0022] c1. Add cerium sulfate, hexaammine cobalt trichloride, ferric chloride, and 68% by mass of concentrated nitric acid to deionized water and mix to form a crystallization solution;
[0023] c2. Immerse the intermediate C in the crystallization solution, heat it in a water bath to 50-70°C, react for 10-16 hours, wash with deionized water, and dry at room temperature for 6-9 hours to complete CeCo2Fe 16 O 27 The crystals are loaded on the surface of the Ni(PDA)2(PANI)2 coordination polymer to finally obtain the foam copper-based composite material.
[0024] Preferably, in step c1, the concentration of cerium sulfate in the crystallization solution is 50-80 g / L, the concentration of ferric chloride is 130-150 g / L, the mass fraction of nitric acid is 3-6%, and the amount of hexaamminecobalt trichloride added per liter of crystallization solution is 80-120 g.
[0025] Preferably, in step c2, the weight of the intermediate C immersed in each liter of the crystallization solution is 220-240 g.
[0026] The positive effects of the present invention are as follows: the copper foam composite material prepared by the method of the present invention first obtains a nickel atom-modified polydopamine / aniline composite organic substance on the basis of forming a polydopamine / aniline composite organic substance on the surface of the copper foam matrix, and then the NH2 group of the polydopamine / aniline composite organic substance modified by the nickel atom on the surface of the copper foam matrix and the nitrogen atom of the NH group provide lone pairs of electrons to share with nickel ions, thereby forming a [Ni(PDA)2(PANI)2] coordination polymer with a complex three-dimensional structure, and finally CeCo2Fe 16 O 27 Crystals. When the [Ni(PDA)2(PANI)2] coordination polymer is irradiated with a certain energy, the electrons in its bonding π orbital will jump to the antibonding π* orbital. These excited electrons will release heat when relaxing back to the ground state, which has an excellent photothermal effect. At the same time, the photothermal effect of the [Ni(PDA)2(PANI)2] coordination polymer can promote the cleavage of the peracetic acid OO bond to generate CH3C(O)OO·, CH3C(O)O· and ·OH free radicals. In addition, the chelation of the amino group and aromatic ring of the [Ni(PDA)2(PANI)2] coordination polymer can effectively increase the oxidative degradation reaction rate of metronidazole. CeCo2Fe 16 O 27 The crystal is a hexagonal system, which can significantly accelerate the electron transfer rate in the degradation process of metronidazole, thereby reducing the activation energy of peracetic acid, further promoting the generation rate and quantity of CH3C(O)OO·, CH3C(O)O· and ·OH free radicals, and effectively improving the degradation effect of metronidazole wastewater.
[0027] In summary, the foam copper-based composite material prepared according to the present invention has excellent photothermal effect and can efficiently activate peracetic acid to degrade metronidazole wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the preparation process of the foam copper-based composite material of the present invention;
[0029] Figure 2 Schematic diagram of the microstructure of the foam copper-based composite material of the present invention;
[0030] Figure 3 It is the photothermal temperature of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention after being irradiated with simulated sunlight for 30 minutes during the treatment of simulated metronidazole-containing sewage;
[0031] Figure 4 The degradation rate of metronidazole in the simulated metronidazole-containing wastewater treated by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0032] Reference Figure 1 The present invention provides a method for preparing a foam copper-based composite material with photothermal effect, comprising the following steps:
[0033] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0034] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 20 to 50 g, the amount of m-phenylenediamine added is 70 to 110 g, the amount of dopamine hydrochloride added is 80 to 100 g, the amount of aminoacetic acid added is 10 to 25 g, and the amount of sodium hydroxide added is 15 to 30 g; add azobisisoheptanitrile to ethanol and mix to form an additive solution, wherein the amount of azobisisoheptanitrile added per liter of the additive solution is 3 0-60g; the base liquid and the additive liquid are mixed in a volume ratio of 9-11:2-3 to form a reaction solution, the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in each liter of the reaction solution is 170-220g), heated to 110-130°C, reacted for 3-5 hours, and the sample is taken out and washed with deionized water to obtain a foam copper with a polydopamine / aniline (PDA / PANI) composite organic material loaded on the surface, which is recorded as intermediate A, wherein the structural formula of the polydopamine / aniline composite organic material is:
[0035]
[0036] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 10 to 25 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 50-70 g), immerse at room temperature for 4-6 hours, remove the sample, wash it with deionized water, and dry it at room temperature for 8-12 hours to obtain a foam copper with a nickel atom-modified polydopamine / aniline composite organic compound on its surface, which is recorded as intermediate B, wherein the structural formula of the nickel atom-modified polydopamine / aniline composite organic compound is:
[0037]
[0038] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer, specifically comprising the following operations:
[0039] b1. Add nickel sulfate, N-methylaniline, sodium pyrosulfite and dopamine hydrochloride to deionized water to form a coordination polymer construction solution (the nickel sulfate concentration in the polymer construction solution is 50 to 80 g / L, the sodium pyrosulfite concentration is 20 to 30 g / L, and the dopamine hydrochloride concentration is 40 to 70 g / L; the amount of N-methylaniline added per liter of polymer construction solution is 10 to 50 ml);
[0040] b2. Immerse the intermediate B in the coordination polymer construction solution (the weight of the intermediate B immersed in each liter of the coordination polymer construction solution is 140-170 g), heat it to 50-90°C in a water bath, react for 10-14 hours, and dry it at room temperature for 6-8 hours to obtain foam copper with Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
[0041] Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16 O 27 Crystal, specifically including the following operations:
[0042] c1. Add cerium sulfate, hexaamine cobalt trichloride, ferric chloride, and 68% concentrated nitric acid to deionized water and mix to form a crystallization solution (the concentration of cerium sulfate in the crystallization solution is 50 to 80 g / L, the concentration of ferric chloride is 130 to 150 g / L, the mass fraction of nitric acid is 3 to 6%, and the amount of hexaamine cobalt trichloride added per liter of crystallization solution is 80 to 120 g);
[0043] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 220-240g), heated to 50-70°C in a water bath, reacted for 10-16 hours, washed with deionized water, and dried at room temperature for 6-9 hours to complete CeCo2Fe 16 O 27 The crystal is loaded on the surface of Ni(PDA)2(PANI)2 coordination polymer, and finally the foam copper-based composite material (foam copper-based [Ni(PDA)2(PANI)2] coordination polymer loaded CeCo2Fe 16 O 27 Crystal), the microstructure diagram is shown in Figure 2 shown.
[0044] The preferred embodiments of the present invention are described below by way of example.
[0045] Example 1
[0046] Preferred embodiment 1 of the present invention provides a method for preparing a foam copper-based composite material with photothermal effect, comprising the following steps:
[0047] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0048] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 40 g, the amount of m-phenylenediamine added is 100 g, the amount of dopamine hydrochloride added is 90 g, the amount of aminoacetic acid added is 20 g, and the amount of sodium hydroxide added is 120 g; add ethanol to form an additive solution, wherein the amount of azobisisoheptanonitrile added per liter of the additive solution is 50 g; the base solution and the additive solution are mixed in a volume ratio of 10:3 to form a reaction solution, and the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in the reaction solution per liter is 210 g), heated to 125 ° C, reacted for 5 hours, and the sample was removed and washed with deionized water to obtain a foam copper with a surface load of polydopamine / aniline composite organic matter, recorded as intermediate A;
[0049] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 20 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 60 g), immerse at room temperature for 5 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 10 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0050] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer, specifically comprising the following operations:
[0051] b1. Nickel sulfate, N-methylaniline, sodium metabisulfite and dopamine hydrochloride were added to deionized water to form a coordination polymer construction solution (the nickel sulfate concentration in the polymer construction solution was 80 g / L, the sodium metabisulfite concentration was 26 g / L, and the dopamine hydrochloride concentration was 60 g / L; the amount of N-methylaniline added per liter of polymer construction solution was 40 ml);
[0052] b2. The intermediate B is immersed in the coordination polymer construction liquid (the weight of the intermediate B immersed in each liter of the coordination polymer construction liquid is 160 g), heated to 80°C in a water bath, reacted for 13 hours, and dried at room temperature for 7 hours to obtain a foam copper with a Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
[0053] Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16O 27 Crystal, specifically including the following operations:
[0054] c1. Cerium sulfate, hexaamine cobalt trichloride, ferric chloride, and 68% concentrated nitric acid were added to deionized water and mixed to form a crystallization solution (the concentration of cerium sulfate in the crystallization solution was 70 g / L, the concentration of ferric chloride was 140 g / L, the mass fraction of nitric acid was 5%, and the amount of hexaamine cobalt trichloride added per liter of crystallization solution was 110 g);
[0055] c2. The intermediate C was immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution was 230 g), heated to 60 ° C in a water bath, reacted for 13 hours, washed with deionized water, and dried at room temperature for 8 hours to complete CeCo2Fe 16 O 27 The crystal is loaded on the surface of Ni(PDA)2(PANI)2 coordination polymer, and finally the foam copper-based composite material (foam copper-based [Ni(PDA)2(PANI)2] coordination polymer loaded CeCo2Fe 16 O 27 Crystal), recorded as Example 1.
[0056] Comparative Example 1
[0057] This comparative example 1 provides a method for preparing a foam copper-based composite material, comprising the following steps:
[0058] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0059] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 25 g, the amount of m-phenylenediamine added is 80 g, the amount of dopamine hydrochloride added is 85 g, the amount of aminoacetic acid added is 15 g, and the amount of sodium hydroxide added is 20 g; add ethanol to form an additive solution, wherein the amount of azobisisoheptanonitrile added per liter of the additive solution is 40 g; the base solution and the additive solution are mixed in a volume ratio of 9:2 to form a reaction solution, and the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in the reaction solution per liter is 180 g), heated to 120 ° C, reacted for 4 hours, and the sample was removed and washed with deionized water to obtain a foam copper with a surface loaded with polydopamine / aniline composite organic matter, recorded as intermediate A;
[0060] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 15 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 55 g), immerse at room temperature for 4 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 9 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0061] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer, specifically comprising the following operations:
[0062] b1. Nickel sulfate, N- methylaniline, sodium metabisulfite and dopamine hydrochloride were added to deionized water to form a coordination polymer construction solution (the nickel sulfate concentration in the polymer construction solution was 60 g / L, the sodium metabisulfite concentration was 25 g / L, and the dopamine hydrochloride concentration was 50 g / L; the amount of N- methylaniline added per liter of polymer construction solution was 20 ml);
[0063] b2. The intermediate B is immersed in the coordination polymer construction liquid (the weight of the intermediate B immersed in each liter of the coordination polymer construction liquid is 150 g), heated to 60°C in a water bath, reacted for 12 hours, and dried at room temperature for 6 hours to obtain a foam copper with a Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as Comparative Example 1.
[0064] Comparative Example 2
[0065] This comparative example 2 provides a method for preparing a foam copper-based composite material, comprising the following steps:
[0066] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0067] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 40 g, the amount of m-phenylenediamine added is 90 g, the amount of dopamine hydrochloride added is 85 g, the amount of aminoacetic acid added is 20 g, and the amount of sodium hydroxide added is 25 g; add ethanol to form an additive solution, wherein the amount of azobisisoheptanonitrile added per liter of the additive solution is 40 g; the base solution and the additive solution are mixed in a volume ratio of 11:2 to form a reaction solution, and the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in the reaction solution per liter is 180 g), heated to 120 ° C, reacted for 4 hours, and the sample was removed and washed with deionized water to obtain a foam copper with a surface load of polydopamine / aniline composite organic matter, recorded as intermediate A;
[0068] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 20 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 55 g), immerse at room temperature for 6 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 9 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0069] Step [2] Loading CeCo2Fe on the surface of nickel-modified polydopamine / aniline composite organic matter 16 O 27 Crystal, specifically including the following operations:
[0070] c1. Add cerium sulfate, hexaamine cobalt trichloride, ferric chloride, and 68% concentrated nitric acid to deionized water and mix to form a crystallization solution (the concentration of cerium sulfate in the crystallization solution is 70 g / L, the concentration of ferric chloride is 135 g / L, the mass fraction of nitric acid is 4%, and the amount of hexaamine cobalt trichloride added per liter of crystallization solution is 90 g);
[0071] c2. The intermediate B was immersed in the crystallization solution (the weight of the intermediate B immersed in each liter of the crystallization solution was 230 g), heated to 60 ° C in a water bath, reacted for 12 hours, washed with deionized water, and dried at room temperature for 7 hours to complete CeCo2Fe 16 O 27 The crystal is loaded on the surface of the nickel atom-modified polydopamine / aniline composite organic matter, and finally the foam copper-based composite material (foam copper-based nickel atom-modified polydopamine / aniline composite organic matter loaded CeCo2Fe 16 O 27 Crystal), recorded as Comparative Example 2.
[0072] In order to analyze the photothermal effect of Example 1, Comparative Example 1 and Comparative Example 2 and the performance of activating peracetic acid to degrade metronidazole-containing sewage, metronidazole was added to deionized water to form simulated metronidazole-containing sewage with a metronidazole concentration of 10 mg / L. 100 ml of simulated metronidazole-containing sewage was poured into beakers respectively, 50 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in beakers respectively, a peracetic acid solution with a mass concentration of 15% was added to simulated metronidazole-containing sewage to make the concentration of peracetic acid 1 mmol / L, and a 300W xenon lamp light source with a wavelength of 550nm was used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for thirty minutes, and an infrared thermal imager was used to measure the photothermal effect temperature of Example 1, Comparative Example 1 and Comparative Example 2 during the process of activating peracetic acid to degrade metronidazole-containing sewage (the results are shown in Figure 2). Figure 3 The concentration of metronidazole in the process of degradation of metronidazole-containing wastewater by light-activated peracetic acid was measured by high performance liquid chromatography (a control group without light was also set up), and the metronidazole degradation rate of the corresponding process was calculated (the results are shown in Figure 4 ). Figure 3 It can be seen that the temperature of Example 1 reaches 78°C when the simulated sunlight is irradiated for 30 minutes, which is significantly higher than 52°C of Comparative Example 1 and 44°C of Comparative Example 2. Figure 4 It can be seen that the photothermal effect of Example 1 under light conditions can effectively activate peracetic acid and then degrade metronidazole-containing wastewater, and its metronidazole degradation rate can reach 93%, which is much higher than 62% of Comparative Example 1 and 54% of Comparative Example 2; at the same time, the metronidazole degradation rates of Example 1, Comparative Example 1 and Comparative Example 2 under the condition of no light and only 1 mmol / L peracetic acid added are only 47%, 31% and 24%, respectively. Under the conditions of no light and no peracetic acid, Example 1, Comparative Example 1 and Comparative Example 2 have basically no degradation effect on the metronidazole-containing wastewater.
[0073] In summary, the foam copper-based composite material prepared according to the present invention has excellent photothermal effect and can efficiently activate peracetic acid to degrade metronidazole wastewater.
[0074] To illustrate in further detail, three additional examples are provided below.
[0075] Example 2
[0076] Preferred embodiment 2 of the present invention provides a method for preparing a foam copper-based composite material with photothermal effect, comprising the following steps:
[0077] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0078] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 20 g, the amount of m-phenylenediamine added is 110 g, the amount of dopamine hydrochloride added is 80 g, the amount of aminoacetic acid added is 10 g, and the amount of sodium hydroxide added is 30 g; add ethanol to form an additive solution, wherein the amount of azobisisoheptanonitrile added per liter of the additive solution is 30 g; the base solution and the additive solution are mixed in a volume ratio of 11:2 to form a reaction solution, and the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in the reaction solution per liter is 170 g), heated to 110 ° C, reacted for 5 hours, and the sample was removed and washed with deionized water to obtain a foam copper with a surface loaded with polydopamine / aniline composite organic matter, recorded as intermediate A;
[0079] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 10 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 50 g), immerse at room temperature for 4 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 8 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0080] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer, specifically comprising the following operations:
[0081] b1. Nickel sulfate, N-methylaniline, sodium metabisulfite and dopamine hydrochloride were added to deionized water to form a coordination polymer construction solution (the nickel sulfate concentration in the polymer construction solution was 50 g / L, the sodium metabisulfite concentration was 30 g / L, and the dopamine hydrochloride concentration was 40 g / L; the amount of N-methylaniline added per liter of polymer construction solution was 10 ml);
[0082] b2. Immerse the intermediate B in the coordination polymer construction solution (the weight of the intermediate B immersed in each liter of the coordination polymer construction solution is 140 g), heat to 90°C in a water bath, react for 10 hours, and dry at room temperature for 6 hours to obtain foam copper with Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
[0083] Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16 O 27 Crystal, specifically including the following operations:
[0084] c1. Cerium sulfate, hexaamine cobalt trichloride, ferric chloride, and 68% concentrated nitric acid were added to deionized water and mixed to form a crystallization solution (the concentration of cerium sulfate in the crystallization solution was 50 g / L, the concentration of ferric chloride was 150 g / L, the mass fraction of nitric acid was 3%, and the amount of hexaamine cobalt trichloride added per liter of crystallization solution was 80 g);
[0085] c2. The intermediate C was immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution was 220 g), heated to 70 ° C in a water bath, reacted for 10 hours, washed with deionized water, and dried at room temperature for 9 hours to complete CeCo2Fe 16 O 27 The crystal is loaded on the surface of Ni(PDA)2(PANI)2 coordination polymer, and finally the foam copper-based composite material (foam copper-based [Ni(PDA)2(PANI)2] coordination polymer loaded CeCo2Fe 16 O 27 crystal).
[0086] Example 3
[0087] Preferred embodiment 3 of the present invention provides a method for preparing a foam copper-based composite material with photothermal effect, comprising the following steps:
[0088] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0089] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 50 g, the amount of m-phenylenediamine added is 70 g, the amount of dopamine hydrochloride added is 100 g, the amount of aminoacetic acid added is 25 g, and the amount of sodium hydroxide added is 15 g; add ethanol to form an additive solution, wherein the amount of azobisisoheptanonitrile added per liter of the additive solution is 60 g; the base solution and the additive solution are mixed in a volume ratio of 9:2 to form a reaction solution, and the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in the reaction solution per liter is 220 g), heated to 130 ° C, reacted for 3 hours, and the sample was removed and washed with deionized water to obtain a foam copper with a surface loaded with polydopamine / aniline composite organic matter, recorded as intermediate A;
[0090] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 25 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 70 g), immerse at room temperature for 6 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 12 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0091] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer, specifically comprising the following operations:
[0092] b1. Nickel sulfate, N- methylaniline, sodium pyrosulfite and dopamine hydrochloride were added to deionized water to form a coordination polymer construction solution (the nickel sulfate concentration in the polymer construction solution was 80 g / L, the sodium pyrosulfite concentration was 20 g / L, and the dopamine hydrochloride concentration was 70 g / L; the amount of N- methylaniline added per liter of polymer construction solution was 50 ml);
[0093] b2. Immerse the intermediate B in the coordination polymer construction solution (the weight of the intermediate B immersed in each liter of the coordination polymer construction solution is 170 g), heat it to 50°C in a water bath, react for 14 hours, and dry it at room temperature for 8 hours to obtain foam copper with Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
[0094] Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16 O 27 Crystal, specifically including the following operations:
[0095] c1. Cerium sulfate, hexaamine cobalt trichloride, ferric chloride, and 68% concentrated nitric acid were added to deionized water and mixed to form a crystallization solution (the concentration of cerium sulfate in the crystallization solution was 80 g / L, the concentration of ferric chloride was 130 g / L, the mass fraction of nitric acid was 6%, and the amount of hexaamine cobalt trichloride added per liter of crystallization solution was 120 g);
[0096] c2. The intermediate C was immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution was 240 g), heated to 50 ° C in a water bath, reacted for 16 hours, washed with deionized water, and dried at room temperature for 6 hours to complete CeCo2Fe 16 O 27 The crystal is loaded on the surface of Ni(PDA)2(PANI)2 coordination polymer, and finally the foam copper-based composite material (foam copper-based [Ni(PDA)2(PANI)2] coordination polymer loaded CeCo2Fe16 O 27 crystal).
[0097] Example 4
[0098] Preferred embodiment 4 of the present invention provides a method for preparing a foam copper-based composite material with photothermal effect, comprising the following steps:
[0099] Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter specifically comprises the following operations:
[0100] a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution, wherein the amount of p-aminobenzoic acid added per liter of the base solution is 35 g, the amount of m-phenylenediamine added is 90 g, the amount of dopamine hydrochloride added is 90 g, the amount of aminoacetic acid added is 16 g, and the amount of sodium hydroxide added is 23 g; add ethanol to form an additive solution, wherein the amount of azobisisoheptanonitrile added per liter of the additive solution is 45 g; the base solution and the additive solution are mixed in a volume ratio of 10:3 to form a reaction solution, and the foam copper sample is immersed in the reaction solution (the weight of the foam copper immersed in the reaction solution per liter is 195 g), heated to 120 ° C, reacted for 4 hours, and the sample was removed and washed with deionized water to obtain a foam copper with a surface load of polydopamine / aniline composite organic matter, recorded as intermediate A;
[0101] a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution, wherein the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 19 g; immerse the intermediate A in the modification solution (the weight of the intermediate A immersed in each liter of the modification solution is 60 g), immerse at room temperature for 5 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 10 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
[0102] Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer, specifically comprising the following operations:
[0103] b1. Nickel sulfate, N- methylaniline, sodium metabisulfite and dopamine hydrochloride were added to deionized water to form a coordination polymer construction solution (the nickel sulfate concentration in the polymer construction solution was 65 g / L, the sodium metabisulfite concentration was 25 g / L, and the dopamine hydrochloride concentration was 55 g / L; the amount of N- methylaniline added per liter of polymer construction solution was 30 ml);
[0104] b2. Immerse the intermediate B in the coordination polymer construction solution (the weight of the intermediate B immersed in each liter of the coordination polymer construction solution is 155 g), heat to 70°C in a water bath, react for 12 hours, and dry at room temperature for 7 hours to obtain foam copper with Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
[0105] Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16 O 27 Crystal, specifically including the following operations:
[0106] c1. Add cerium sulfate, hexaamine cobalt trichloride, ferric chloride, and 68% concentrated nitric acid by mass to deionized water and mix to form a crystallization solution (the concentration of cerium sulfate in the crystallization solution is 65g / L, the concentration of ferric chloride is 140g / L, the mass fraction of nitric acid is 5%, and the amount of hexaamine cobalt trichloride added per liter of crystallization solution is 100g);
[0107] c2. The intermediate C was immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution was 230 g), heated to 60 ° C in a water bath, reacted for 13 hours, washed with deionized water, and dried at room temperature for 9 hours to complete CeCo2Fe 16 O 27 The crystal is loaded on the surface of Ni(PDA)2(PANI)2 coordination polymer, and finally the foam copper-based composite material (foam copper-based [Ni(PDA)2(PANI)2] coordination polymer loaded CeCo2Fe 16 O 27 crystal).
[0108] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a foam copper-based composite material with photothermal effect, characterized in that: The following steps are included: Step [1] loading nickel atoms on the surface of the copper foam substrate to modify the polydopamine / aniline composite organic matter; Step [2] converting the nickel atom-modified polydopamine / aniline organic complex on the surface of the copper foam substrate into a Ni(PDA)2(PANI)2 coordination polymer; Step [3] Loading CeCo2Fe on the surface of Ni(PDA)2(PANI)2 coordination polymer 16 O 27 Crystal.
2. The method for preparing a foam copper-based composite material with photothermal effect according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add p-aminobenzoic acid, m-phenylenediamine, dopamine hydrochloride, aminoacetic acid and sodium hydroxide to deionized water and mix to form a base solution; add azobisisoheptanenitrile to ethanol and mix to form an additive solution; mix the base solution and the additive solution in a certain proportion to form a reaction solution, immerse the foam copper sample in the reaction solution, heat to 110-130°C, react for 3-5 hours, take out the sample and wash it with deionized water to obtain a foam copper with a polydopamine / aniline composite organic compound loaded on the surface, recorded as intermediate A; a2. Add bis(1,5-cyclooctadiene)nickel to tetrahydrofuran and mix to form a modification solution; immerse the intermediate A in the modification solution at room temperature for 4-6 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 8-12 hours to obtain a foam copper with a surface loaded with nickel atoms modified polydopamine / aniline composite organic matter, which is recorded as intermediate B.
3. The method for preparing a foam copper-based composite material with photothermal effect according to claim 2, characterized in that: In step a1, the amount of p-aminobenzoic acid added per liter of the base liquid is 20-50g, the amount of m-phenylenediamine added is 70-110g, the amount of dopamine hydrochloride added is 80-100g, the amount of aminoacetic acid added is 10-25g, and the amount of sodium hydroxide added is 15-30g; the amount of azobisisoheptanenitrile added per liter of the additive liquid is 30-60g; the volume ratio between the base liquid and the additive liquid in the reaction liquid is 9-11:2-3; the weight of the foam copper immersed in each liter of the reaction liquid is 170-220g.
4. The method for preparing a foam copper-based composite material with photothermal effect according to claim 2, characterized in that: In step a2, the amount of bis(1,5-cyclooctadiene)nickel added to each liter of the modification solution is 10-25 g; the weight of the intermediate A immersed in each liter of the modification solution is 50-70 g.
5. The method for preparing a foam copper-based composite material with photothermal effect according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add nickel sulfate, N-methylaniline, sodium metabisulfite and dopamine hydrochloride to deionized water to form a coordination polymer construction solution; b2. The intermediate B is immersed in the coordination polymer construction solution, heated to 50-90°C in a water bath, reacted for 10-14 hours, and dried at room temperature for 6-8 hours to obtain a foam copper with Ni(PDA)2(PANI)2 coordination polymer loaded on the surface, which is recorded as intermediate C.
6. The method for preparing a foam copper-based composite material with photothermal effect according to claim 5, characterized in that: In step b1, the concentration of nickel sulfate in the polymer construction solution is 50-80 g / L, the concentration of sodium pyrosulfite is 20-30 g / L, and the concentration of dopamine hydrochloride is 40-70 g / L; the amount of N-methylaniline added per liter of polymer construction solution is 10-50 ml.
7. The method for preparing a foam copper-based composite material with photothermal effect according to claim 5, characterized in that: In step b2, the weight of the intermediate B immersed in each liter of the coordination polymer construction solution is 140-170 g.
8. The method for preparing a foam copper-based composite material with photothermal effect according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add cerium sulfate, hexaammine cobalt trichloride, ferric chloride, and 68% by mass of concentrated nitric acid to deionized water and mix to form a crystallization solution; c2. Immerse the intermediate C in the crystallization solution, heat it in a water bath to 50-70°C, react for 10-16 hours, wash with deionized water, and dry at room temperature for 6-9 hours to complete CeCo2Fe 16 O 27 The crystals are loaded on the surface of the Ni(PDA)2(PANI)2 coordination polymer to finally obtain the foam copper-based composite material.
9. The method for preparing a foam copper-based composite material with photothermal effect according to claim 8, characterized in that: In step c1, the concentration of cerium sulfate in the crystallization solution is 50-80 g / L, the concentration of ferric chloride is 130-150 g / L, the mass fraction of nitric acid is 3-6%, and the amount of hexaamminecobalt trichloride added per liter of crystallization solution is 80-120 g.
10. The method for preparing a foam copper-based composite material with photothermal effect according to claim 8, characterized in that: In step c2, the weight of the intermediate C immersed in each liter of the crystallization solution is 220-240 g.
Citation Information
Patent Citations
Preparation method of photocatalytic air purification material
CN108465461A
Nano composite material, and preparation method and application thereof
CN113321234A
Polydopamine modified carbon nitride / titanium dioxide loaded foamed nickel composite photocatalyst as well as preparation method and application thereof
CN113856757A
Preparation method of foamy copper-based composite organic compound layer catalytic material
CN118594618A
Composite of porous substrate and one-dimensional nanomaterial and method for preparing the same, surface-modified composite and method for preparing the same
US20130045857A1